iPad for seniors in easy steps : covers all models with iPadOS 18 - Vandome, Nick (In Easy Steps, 2024)
The iPad is a tablet computer that is stylish, versatile, and easy to use, and there is no reason why it should be the preserve of the younger generation. The range of models has been expanded over the years so that there are now different sizes to cover all mobile computing requirements. This edition gives the reader all the essential information they need to know to make the most out of their iPad.